Repeat After Me: Affective Scaffolding for Arabic Speaking Fluency - Segaf Baharun; Moh. Tohiri Habib; Nurul Azira; Adham Hasif (Universitas Islam Negeri Palangka Raya Raya, 2026)
Despite the widespread use of repetition in Arabic speaking instruction, empirical research examining its affective scaffolding dimension particularly teacher vocal modulation as an emotional and psychomotor support remains limited.This study investigates the role of affective scaffolding in enhancing Arabic speaking fluency through the “Repeat After Me” technique in a pesantren-based classroom. Using a quasi-experimental mixed-method design, sixty male students were divided into experimental and control groups over eight weeks of instruction. The experimental group received teacher-guided vocal scaffolding involving tone modulation, rhythmic pacing, and empathetic feedback, while the control group practiced standard repetition. Quantitative results revealed significant improvements in fluency (Cohen’s d = 0.89) and a notable reduction in language anxiety among the experimental group. Qualitative findings from interviews indicated that collective repetition fostered emotional safety, enjoyment, and imitation of native-like pronunciation, despite physical fatigue. The integration of affective and psychomotor elements transformed repetition into an engaging, embodied learning process that strengthened confidence and rhythmical accuracy. This study concludes that teacher vocal modulation functions as both an emotional regulator and a psychomotor model, offering a holistic framework for Arabic language pedagogy that unites sound, emotion, and bodily expression.